2006
DOI: 10.1007/s00027-006-0853-2
|View full text |Cite
|
Sign up to set email alerts
|

Biological diversity of peatlands in Canada

Abstract: Knowledge about the biodiversity of Canada's vast peatlands is poor largely because peatlands have not been routinely differentiated from other types of habitats. Plants are better known than the animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 100 publications
1
21
1
1
Order By: Relevance
“…There are many different spring types, and the early diatom studies mostly concentrated on specifi c habitats: thermal (BÍLÝ 1934, BRABEZ 1941, DELL'UOMO 1986, LE-DERER et al 1998, KAŠTOVSKÝ and KOMÁREK 2001, HINDÁK and HINDÁKOVÁ 2006, saline (KADLUBOWSKA 1985), tufa (PENTECOST 1991(PENTECOST , 1998 and acid (CAMBRA and HINDÁK 1998). More recently springs and especially Alpine springs have attracted the attention of biologists and conservationists due to the high share of endangered species and specialists found in their communities (e.g., CANTONATI 1998, PEINTINGER et al 2003, CANTONATI et al 2006, WARNER and ASADA 2006, HÁJEK et al 2006, PAYNE and MITCHELL 2007.…”
Section: Introductionmentioning
confidence: 99%
“…There are many different spring types, and the early diatom studies mostly concentrated on specifi c habitats: thermal (BÍLÝ 1934, BRABEZ 1941, DELL'UOMO 1986, LE-DERER et al 1998, KAŠTOVSKÝ and KOMÁREK 2001, HINDÁK and HINDÁKOVÁ 2006, saline (KADLUBOWSKA 1985), tufa (PENTECOST 1991(PENTECOST , 1998 and acid (CAMBRA and HINDÁK 1998). More recently springs and especially Alpine springs have attracted the attention of biologists and conservationists due to the high share of endangered species and specialists found in their communities (e.g., CANTONATI 1998, PEINTINGER et al 2003, CANTONATI et al 2006, WARNER and ASADA 2006, HÁJEK et al 2006, PAYNE and MITCHELL 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Peatland ecosystems have recently been in the spotlight because of their unique flora and fauna, which include many rare species (Rydin and Jeglum 2006;Spitzer and Danks 2006;Warner and Asada 2006), but very few studies have examined the fauna comprising peatlands. Rosenberg and Danks (1987) suggested that some aquatic invertebrates have evolved several traits, such as precise microhabitat selectivity, to avoid food limitation, desiccation, and anoxia in peatlands.…”
Section: Introductionmentioning
confidence: 99%
“…peatlands are important for biodiversity, as numerous species of invertebrates, birds and 49 bryophytes are restricted to such habitats (Warner & Asada, 2006). On both local and global scales, peatlands have been damaged through drainage and peat extraction, but 51 attempts are now being made to restore them through ecological engineering techniques.…”
mentioning
confidence: 99%